Nature conservation policies are biased toward forests and neglect grassy ecosystems worldwide - Pillar, Valério D.; Overbeck, Gerhard E. (Science (American Association for the Advancement of Science), 2025)
Globally, grassy ecosystems (including grasslands, savannas, shrublands, woodlands, and tundra) cover 30 to 40% of the land and provide important benefits such as climate change mitigation and adaptation, livestock production, and cultural services. However, despite their importance, the conservation of grassy ecosystems—compared with that of forests—has been neglected around the world, leading to a greater loss rate than forest ecosystems in many regions . Here, we examine this bias in public conservation discourse and policies that give priority to forests and neglect the conservation of grassy ecosystems worldwide. We argue that grassy ecosystems need stronger legal safeguards and global recognition to match forest conservation efforts.